PENERAPAN STRUCTURAL EQUATION MODELLING (SEM) AMOS PADA KOMITMEN ORGANISASI DAN PRESTASI KERJA (Studi Kasus: Bidan Puskesmas di Banyumas, Jawa Tengah, Indonesia) - Suyoto Suyoto; Ahmad Zainal Abidin; Hariyaty Hariyaty (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2019)
This study aims to determine the application of Structural Equation Modeling (SEM) Analysis of Moment Structure (AMOS) to the organizational commitment and work performance of the Midwife of Public Health Centre in Banyumas Regency. Central Java, Indonesia. Data collection techniques using purposive sampling. The sample of this study were 243 midwives with the following criteria: minimum education D3 midwifery, minimum working period of one year and minimum age of 22 years. The data analysis technique uses SEM AMOS. Model fit is shown by good and significant goodness of fit results. The results showed that indicators of organizational commitment consisting of affective commitment, continuous commitment and normative commitment were able to explain the construct of organizational commitment. Work performance indicators consisting of work performance, contextual performance, adaptive performance and productive work performance can explain the construct of work performance. The construct of organizational commitment has a significant positive effect on the construct of work performance.